Children Daily Eating Behavior and Sugar Consumption Pattern: A Phenomenological Study - Grace Vita Anggi Roma Uli Simbolon; Samuel Maju Simanjuntak (Jurnal Berita Ilmu Keperawatan, 2023)
The pattern of food consumption is a picture of the type of food consumed, the amount of food consumed, and the lifestyle of the community. The pattern of eating is formed in the same way as a person's eating habits. The habit of consuming sugar among children can also be associated with the existence of several health problems such as diabetes mellitus. This study aims to explore and find consumption patterns of daily food and fluid intake in the age group of children that contain sugar in the community around Parongpong, West Bandung. and themes that will conclude the phenomenon of consumption and dependence on sugar in community groups. This research is a qualitative phenomenological study, where the aim is to reduce the individual experience of a phenomenon into a description that finds the universal essence of the phenomenon. 7 key informants were voluntarily involved in this study. The verbatim data were analyzed for their ethical and emic meanings using the Colaizzi method. The results of the analysis of the data obtained during the interviews were able to bring up 6 sub-themes. The six sub-themes raised 3 major themes, namely consumption patterns of daily sugar intake for the youth age group, understanding the need for change and approaches to reducing sugar intake, and types of approaches in changing sugar consumption patterns for adolescents.